Private Higher Education in the United Kingdom - Hunt, Stephen A.; Boliver, Vikki (International Higher Education, 2019)
The UK government is keen to expand the private higher education (HE) sector to establish a more market driven alternative to public HE. However, private HE in the United Kingdom has been subject to little official oversight, and little data has been gathered concerning it. Our research is an attempt to conduct a comprehensive web-based survey of the private HE sector. We found only five private universities, but over 800 private providers in operation in the United Kingdom, with the greater proportion located in Southeast England, London in particular. The sector concentrates on specialist provision and professional training, along with subjects typical of private HE globally, business administration and health-related courses, often at a subdegree level. While private HE answers to a demand, there is little to indicate that the private HE sector amounts to a competitive alternative to the public HE system.